Rheological changes in bitumen caused by aging and by the interaction with rubber - Peralta, J. (2009)
The use of bitumen modified with crumb rubber contributes for a sustainable development of road infrastructures. However, the increasing demands on quality and durability of pavements lead lo the need of a profound knowledge in the physicochemical changes of the materials which constitute these AR binders. In this work several base bitumens interacted with crumb rubber in order to produce AR binders, which were subsequently separated, by using a modified “Basket drainage method” to recover the residual bitumens. The effect of aging during the laying procedures was also studied by using the RTFOT test. Additionally, a new “Sphere AR production simulator” method was developed to simulate the bitumen aging without the contribution of the rubber The DSR was used lo evaluate the chemical and rheological changes in the properties of AR binders. In this work, reduced changes were observed in the binder due lo the interaction with crumb rubber